2022
DOI: 10.1371/journal.pone.0275639
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnostic evaluation of symptomatic breast cancer in sub-Saharan Africa: A qualitative study of Tanzanian women

Abstract: Background Women with breast cancer in sub-Saharan Africa are commonly diagnosed at advanced stages. In Tanzania, more than 80% of women are diagnosed with stage III or IV disease, and mortality rates are high. This study explored factors contributing to delayed diagnostic evaluation among women with breast cancer in Tanzania. Methods A qualitative study was performed at Muhimbili National Hospital in Dar es Salaam, Tanzania. Twelve women with symptomatic pathologically proven breast cancer were recruited. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Three-quarters (72.9%) of clients with con rmed malignant lesions had staging and with over half (59.25%) with a late diagnosis and were enrolled in palliative care without the ability for curative treatment. just like another study on late breast cancer diagnosis done in Tanzania found [41]. This might be attributed to the late identi cation of clients due to low overall screening in the district (only 11% of women 15-49 years by March 2022), leading to late diagnosis followed by late enrollment into the tumor board.…”
Section: Discussionmentioning
confidence: 87%
“…Three-quarters (72.9%) of clients with con rmed malignant lesions had staging and with over half (59.25%) with a late diagnosis and were enrolled in palliative care without the ability for curative treatment. just like another study on late breast cancer diagnosis done in Tanzania found [41]. This might be attributed to the late identi cation of clients due to low overall screening in the district (only 11% of women 15-49 years by March 2022), leading to late diagnosis followed by late enrollment into the tumor board.…”
Section: Discussionmentioning
confidence: 87%
“…In some parts of the world, symptomatic presentation of breast cancer is the only way breast cancer is diagnosed (e.g., sub‐Saharan Africa and India) 35–37 . In Ontario, Canada, use of a dedicated breast assessment unit is associated with shorter time to diagnosis for patients with symptomatic breast cancer 38 .…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] In a study conducted in 1991-1992, In some parts of the world, symptomatic presentation of breast cancer is the only way breast cancer is diagnosed (e.g., sub-Saharan Africa and India). [35][36][37] In Ontario, Canada, use of a dedicated breast assessment unit is associated with shorter time to diagnosis for patients with symptomatic breast cancer. 38 In the United Kingdom, symptomatic breast cancer units are part of the National Health Service clinic system with patients generally presenting with later stage breast cancer and different demographics from screened patients.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
“…According to WHO, breast cancer is the most frequent cancer among women, impacting 2.1 million women each year, and causes the greatest number of cancer-related deaths among women [6]. Approximately half of all women diagnosed with breast cancer in Tanzania die of the disease [7] and approximately 80% of women diagnosed with breast cancer in Tanzania happen at advanced stages (III or IV), when treatment is less effective and outcomes are poor [4,5]. It is predicted that by 2030, new breast cancer cases will increase by 82% [4,5].…”
Section: Introductionmentioning
confidence: 99%